The Effect of Self-Efficacy and Learning Independence on Students Mathematical Reasoning Ability : (Survey at Class VII Public Junior High School in Bekasi City) - Chandra Sagul Haratua; Ria Nur Indriasari; Yuana Yuana; Muhammad Maksudi; Lorensius Gabun; Natania Amanda (CV. Publikasi Indonesia, 2024)
The purpose of the research is to determine 1) Direct influence of self-efficacy on students' math reasoning ability 2) the Direct influence of learning independence on the ability of mathematical reasoning 3) the Direct influence of self-efficacy on student self-reliance 4). The indirect effect of self-efficacy on mathematical reasoning ability through student learning independence. This research used a survey method. The independent variables bound to this research are Self Efficacy (X1), Learning Independence (X2), and Mathematical Reasoning Ability (X3). The research method used surveys. The sample used is 100 students as a research sample by using a proportional random sampling technique from all students of class VII of National Junior High School in Bekasi City. The data were collected using math-reasoning test and self-efficacy questionnaire and learning independence. Hypothesis testing with path analysis (Path Analys). This study was conducted in January 2018. Based on the results of the hypothesis and data analysis concluded several things as follows (1) There is a direct influence of self-efficacy significant to the ability of mathematics reasoning of students of National Junior High School in Bekasi City. This is evidenced by the acquisition of tcount (4.615)> ttable (1.984). (2) There is a significant direct influence of learning independence to the students' math skills ability in National Junior High School in Bekasi City. This is evidenced by the acquisition of tcount (5.869)> ttable (1.984). (3) There is a direct influence of self-efficacy significantly to the independence of students studying National Junior High School in Bekasi City. This is evidenced by the acquisition of tcount (18,719) > ttable (1,984). (4) There is a significant indirect influence of self-efficacy of students to the ability of mathematical reasoning through the independence of students studying National Junior High School in Bekasi City. This is evidenced by the acquisition of tcount (6.4728) > ttable (1.984). The implications of this research are 1). To improve the ability of mathematical reasoning can be done by improving self-efficacy and student learning independence. 2) to improve learning independence is done by improving self-efficacy.